2022
DOI: 10.3389/fimmu.2022.957201
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune-complexes of IgG/IgM bound to B2-glycoprotein-I associated with complement consumption and thrombocytopenia in antiphospholipid syndrome

Abstract: BackgroundAntiphospholipid syndrome (APS) is a multisystemic autoimmune disorder characterized by thrombotic events and/or gestational morbidity in patients with antiphospholipid antibodies (aPL). In a previous single center study, APS-related clinical manifestations that were not included in the classification criteria (livedo reticularis, thrombocytopenia, leukopenia) were associated with the presence of circulating immune-complexes (CIC) formed by beta-2-glycoprotein-I (B2GP1) and anti-B2GP1 antibodies (B2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…This observation associated with the finding that whereas thrombotic APS displayed more IgG aPL reactivities than obstetric APS, IgM aPL reactivities were more prevalent in OAPS. The idea that IgM isotypes are more prevalent in gestational than thrombotic APS, and vice versa, was also observed recently in a study describing the prevalence of circulating β2GPI-aβ2GPI immune complexes [ 36 ].…”
Section: Discussionmentioning
confidence: 62%
“…This observation associated with the finding that whereas thrombotic APS displayed more IgG aPL reactivities than obstetric APS, IgM aPL reactivities were more prevalent in OAPS. The idea that IgM isotypes are more prevalent in gestational than thrombotic APS, and vice versa, was also observed recently in a study describing the prevalence of circulating β2GPI-aβ2GPI immune complexes [ 36 ].…”
Section: Discussionmentioning
confidence: 62%
“…In line with this, our data showed that patients with PAPS with triple positivity had fewer PLT compared to that in non‐triple‐positive patients. Complement levels are associated with the disease activity of APS 63,64 . Studies have shown that the levels of C3 and C4 are decreased in patients with APS with thrombotic events, 63 and the reduced complement levels are associated with the increased risk of APOs 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The proteome of monocytes treated with thrombotic APS IgG was further described using label-free proteomics. Among the 12 most reliable proteins associated with the cytoskeleton, immune response, and coagulation function, POTEE and b-actin-like protein 3 overlapped with 2D DiGE, Abnormalities in the regulation of these proinflammatory and procoagulant proteins could serve as targets for subsequent treatment and contribute to a deeper understanding of the diversity of APS pathogenesis (186). Urine proteomics has recently been reported as a noninvasive method to distinguish primary thrombotic APS from primary obstetric APS.…”
Section: Antiphospholipid Syndrome (Aps)mentioning
confidence: 99%